REVIEW OF MIH SYNDROME TREATMENT IN CHILDREN AND ADOLESCENTS - Oana Adina Minut; Oana Enciu; Ana Sirghe; Vasilica Toma; Cristian Marius Toma; Alina-Elena Adumitroaie; Simina-Mădălina Vacariu; Gabriela Geletu (Romanian Society of Oral Rehabilitation, 2022)
Molar incisor hypomineralization syndrome (MIH) is considered to be a 21st century disease, but it was studied for a long time in dental medicine, as it poses clinical problems for dentists around the world, especially in children and adolescents. This study aims to evaluate treatment methods available in literature for teeth affected by MIH syndrome. Materials and method Information were obtained by evaluating electronic databases PubMed and Web of Science and performing a review of literature containing basic science and clinical studies regarding MIH syndrome in children and adolescents. In total, a number of 54 scientific articles were selected and evaluated, after applying the MeSH search terms: "MIH syndrome", "treatment", "children and adolescents". Results Preventive strategies, treatment options and management guidelines are available in literature, and each clinician should carefully evaluate their implementation depending on the severity of the syndrome and the age of the child. Conclusions Management of MIH syndrome is complex and difficult considering the morpho-functional, psycho-social and economic aspects of the disease, but possibilities are varied and dentists should always be up to date with treatment protocols. Some of the treatment methods available today are presented in this review.